2013
DOI: 10.1182/blood-2012-12-471938
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of PKCα and PKCθ prevents GVHD while preserving GVL activity in mice

Abstract: Key Points PKCα and PKCθ cooperate in T-cell alloresponses, which contribute to GVHD. Pharmacologic inhibition of PKCα and PKCθ prevents GVHD and largely preserves GVL responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
(53 reference statements)
1
39
0
Order By: Relevance
“…This is of enormous benefit for patients receiving allogeneic BMT. Similar results were obtained by Haarberg et al [25]: Consistent with the data obtained from the cardiac allograft experiments [23], the concomitant deficiency of PKCθ and PKCα allowed protection against GvHD in an additive manner. On the other hand, genetic deficiency of PKCθ rendered mice more prone to a Moloney murine leukaemia virus (M-MuLV)-induced leukaemia [26], suggesting a partially compromised anti-tumour host response in PKCθ-deficient mice.…”
Section: Pkcθ In Transplantation Medicinesupporting
confidence: 89%
“…This is of enormous benefit for patients receiving allogeneic BMT. Similar results were obtained by Haarberg et al [25]: Consistent with the data obtained from the cardiac allograft experiments [23], the concomitant deficiency of PKCθ and PKCα allowed protection against GvHD in an additive manner. On the other hand, genetic deficiency of PKCθ rendered mice more prone to a Moloney murine leukaemia virus (M-MuLV)-induced leukaemia [26], suggesting a partially compromised anti-tumour host response in PKCθ-deficient mice.…”
Section: Pkcθ In Transplantation Medicinesupporting
confidence: 89%
“…Data are presented for individual GVHD target organs. All slides for GVHD analysis were coded and read in a blinded fashion (48).…”
Section: Methodsmentioning
confidence: 99%
“…Because GVHD prevention can be achieved by modulation of Tcell migration to organ sites (25)(26)(27), we speculated that ruxolitinib may induce a reduced T-cell recruitment to GVHD targets. Indeed, the immunohistochemical quantification of T-cell (CD3 epsilon þ ) infiltration into GVHD target organs at day 14 post-BMT revealed that treatment with ruxolitinib reduced T-cell numbers in the skin [number of intraepithelial (IEL) cells/skin length: 47 AE 5 vs. 2.5 AE 0.7; P < 0.0001; Fig.…”
Section: Ruxolitinib Treatment Reduced Overall T-cell Infiltrates In mentioning
confidence: 99%